Depression as an Escape from Burden of Life - Bartoskova, Magda (Journal of Education Culture and Society, 2020)
This study aims to explore the inner world of people suffering from depressive disorder. Four people hospitalized in Prague Psychiatric Centre were interviewed. Method of Grounded Theory and discursive analysis revealed a specific way of depressive thinking and experiencing the self and the outer world. Depressive individuals manifest deficit in introspection. They do not perceive themselves as the authors of their lives and they show a tendency to look for external, estranged meanings of life. Combination of these attributes was found to be possible psychological cause leading towards the outburst of depressive disorder. Significant similarities were found between research results and C.G. Jung´s understanding of depressed people, which he describes through energetic model of libido.